Cardiovascular risk prediction using physical performance measures in COPD: results from a multicentre observational study. Issue 12 (28th December 2020) - Fermont, Jilles M; Fisk, Marie; Bolton, Charlotte E; MacNee, William; Cockcroft, John R; Fuld, Jonathan; Cheriyan, Joseph; Mohan, Divya; Mäki-Petäjä, Kaisa M; Al-Hadithi, Ali B; Tal-Singer, Ruth; Müllerova, Hana; et al.
Abstract : Objectives: Although cardiovascular disease (CVD) is a common comorbidity associated with chronic obstructive pulmonary disease (COPD), it is unknown how to improve prediction of cardiovascular (CV) risk in individuals with COPD. Traditional CV risk scores have been tested in different populations but not uniquely in COPD. The potential of alternative markers to improve CV risk prediction in individuals with COPD is unknown. We aimed to determine the predictive value of conventional CVD risk factors in COPD and to determine if additional markers improve prediction beyond conventional factors. Design: Data from the Evaluation of the Role of Inflammation in Chronic Airways disease cohort, which enrolled 729 individuals with Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage II–IV COPD were used. Linked hospital episode statistics and survival data were prospectively collected for a median 4.6 years of follow-up. Setting: Five UK centres interested in COPD. Participants: Population-based sample including 714 individuals with spirometry-defined COPD, smoked at least 10 pack years and who were clinically stable for >4 weeks. Interventions: Baseline measurements included aortic pulse wave velocity (aPWV), carotid intima–media thickness (CIMT), C reactive protein (CRP), fibrinogen, spirometry and Body mass index, airflow Obstruction, Dyspnoea and Exercise capacity (BODE) Index, 6 min walk test (6MWT) and 4 m gait speed (4MGS) test. Primary and secondary outcome measures: New occurrence (first event) of fatal or non-fatal hospitalised CVD, and all-cause and cause-specific mortality. Results: Out of 714 participants, 192 (27%) had CV hospitalisation and 6 died due to CVD. The overall CV risk model C-statistic was 0.689 (95% CI 0.688 to 0.691). aPWV and CIMT neither had an association with study outcome nor improved model prediction. CRP, fibrinogen, GOLD stage, BODE Index, 4MGS and 6MWT were associated with the outcome, independently of conventional risk factors (p<0.05 for all). However, only 6MWT improved model discrimination (C=0.727, 95% CI 0.726 to 0.728). Conclusion: Poor physical performance defined by the 6MWT improves prediction of CV hospitalisation in individuals with COPD. Trial registration number: ID 11101.